Can you move -1 from -x to the other side of the equation without bringing x?

For example:
y = -x +b

Can I move - 1 to y without bringing x?
I am little perplexed with your question! As such I do not see, explicitly, any (-1) in your equation.

y = -x + b ............................................... (1)

However, you can claim that, implicitly, the equation is:

y = (-1) * x + b

In that case you can multiply both sides of the equation by (-1) - giving you:

(-1) * y = (-1) * [(-1) * x + b]

-y = (-1) * (-1) * x + (-1) * b

-y = x - b ............................................(2)

The given equation (1) and the resulting equation (2) are equivalent. You should observe the "signs" of all the elements of the equation/s and how did those change.
 
Suppose x=100. Then -x=-100. I think that you are saying that you want to bring the -1 to the other side by addition. So using your method you will get x=-100 + 1= -99. But it can't be that x=-99 as it was given that x= 100.
As already pointed out, to get -x to become x you need to multiply by -1
 
Stop, stop, stop, saying, writing, or even thinking "move from one side of the equation to the other"! There are many different ways to "move" number or variable from one side of the equation to the other and each requires different handling.

You have the equation "y = -x +b" and ask "Can I move - 1 to y without bringing x?". What is it that you really want to do? I suspect you want to change "-x" to "x". there are three ways to "change -x to x": You could add 2x, so that 2x- x= x, you could multiply by -1, so that -1(-x)= x, or you could divide by -1, so that -x/(-1)= x. The last two are essentially the same thing. And, of course, any of those thaT you do to one side of the equation, you also have to the other side.

Given y= -x+ b, adding 2x to both sides gives y+ 2x= x+ b, probably not what you want. Multiplying or dividing by -1 gives -y= x- b and then you move b to the other side add b to both sides to get b- y= x.
 
Stop, stop, stop, saying, writing, or even thinking "move from one side of the equation to the other"! There are many different ways to "move" number or variable from one side of the equation to the other and each requires different handling.

You have the equation "y = -x +b" and ask "Can I move - 1 to y without bringing x?". What is it that you really want to do? I suspect you want to change "-x" to "x". there are three ways to "change -x to x": You could add 2x, so that 2x- x= x, you could multiply by -1, so that -1(-x)= x, or you could divide by -1, so that -x/(-1)= x. The last two are essentially the same thing. And, of course, any of those thaT you do to one side of the equation, you also have to the other side.

Given y= -x+ b, adding 2x to both sides gives y+ 2x= x+ b, probably not what you want. Multiplying or dividing by -1 gives -y= x- b and then you move b to the other side add b to both sides to get b- y= x.
You can also add x to both sides to get x.
 
Yes, to get x on the other side. I interpreted the original post to mean "change -x to x where it stands".
 
Top